Systematic improvement of value streams – fundamentals of value stream oriented process management. (1st January 2013) - Kuhlang, Peter; Hempen, Sabine; Sihn, Wilfried; Deuse, Jochen
Improving processes is a daily base challenge for enterprises. In particular improvement attempts occur in various different levels of detail and are commonly not linked methodically. Process management systems in general are suitable approaches to manage process improvements. A systematic routine to improve processes and value stream mapping (VSM) are integrated into the organisational framework of process management in order to enable a methodically fostered improvement of value streams in different levels of detail. The outlined approach to systematise the application of VSM is the conjunction of volatile and short-cyclic improvements of a value stream and the determination of target-conditions in order to develop the value stream towards an ideal-state which is specified by productivity and quality criteria.